2020
DOI: 10.2196/17818
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning and Smartphone and Smartwatch Data to Detect Emotional States and Transitions: Exploratory Study

Abstract: Background Emotional state in everyday life is an essential indicator of health and well-being. However, daily assessment of emotional states largely depends on active self-reports, which are often inconvenient and prone to incomplete information. Automated detection of emotional states and transitions on a daily basis could be an effective solution to this problem. However, the relationship between emotional transitions and everyday context remains to be unexplored. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…With the RBF kernel, an SVM classifier, a linear classifier, can classify nonlinear data sets [ 63 , 64 ]. These algorithms have been used in previous work [ 65 - 69 ] on mental health studies. We used the same pooled and imputed data set from statistical analysis, but ensured that all records are distinct.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the RBF kernel, an SVM classifier, a linear classifier, can classify nonlinear data sets [ 63 , 64 ]. These algorithms have been used in previous work [ 65 - 69 ] on mental health studies. We used the same pooled and imputed data set from statistical analysis, but ensured that all records are distinct.…”
Section: Methodsmentioning
confidence: 99%
“…However, the proportion of each class is still dependent on its availability in the data set. We handled class imbalance in the training data set with the synthetic minority over-sampling technique (SMOTE) [ 65 , 73 , 74 ], which generates synthetic data for the minority class, resulting in a balanced training data set.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, defining a-priori model is impossible. However, a range of approaches will be tested, this includes: Random Forest models, Support Vector Machine (SVM), XGBoost (XGB), K-Nearest Neighbor (KNN), and Logistic Regression [LR; (110)(111)(112)(113)(114)].…”
Section: Mobile Sensingmentioning
confidence: 99%
“…Research by Pratap et al [ 43 ] found that mobility and smartphones’ normal usage has the potential to predict an individual’s mood state changes using personalized models. Further important work was published recently by Sultana, Al-Jefri and Lee [ 45 ], in which machine learning algorithms were used to analyze varied data recorded from individuals’ smartphones and smartwatches to determine emotional states and transitions.…”
Section: The Digital Revolution In Mental Healthmentioning
confidence: 99%